Analysis on Nodes and Elements for IoT Industrial Chain - Lehu Lin (Dianxin kexue)
In recent years，the internet of things has been paid wide attention and gets rapid development in our country，which is regarded as one of the key emerging industries to promote the growth of our economy. However， since the development of the internet of things is still in its infancy，the empirical research from the perspective of industry chain is still lacking. On the basis of summarizing the current situation of the development of the internet of things industry chain，Delphi method and Q-sort method were used to research the internet of things industry chain nodes and core elements with the combination of qualitative and quantitative method. The key elements of the internet of things industry chain development was determined，and related suggestions were put forward.